A current study on ballasted rail tracks in Sri Lanka. - Venuja, S.; Navaratnarajah, S.K. (Institution of Engineers, Sri Lanka, 2022)
Rail transport was introduced in Sri Lanka in the early 1860s for transporting coffee from estates to the port. Sri Lanka Railways (SLR) is the only rail transport organization in Sri Lanka which was established in 1864 under the name of Ceylon Government Railway. The total route length of ten main lines and three spur lines is 1,607 km. The track gauge is 1676 mm and the sleeper length is 2790 mm. Generally, rail tracks are made of either using ballast or concrete. The initial construction cost for slab tracks is much higher than that for ballasted tracks. Most of the tracks in Sri Lanka are also ballasted rail tracks. The primary components in ballasted tracks are steel rail, concrete or timber sleeper, fastening system, ballast layer, sub-ballast layer, and compacted subgrade (See Figure 1(a) and (b)). The ballast layer is the largest layer by volume and weight. Ballast is a coarse granular material with various-sized particles, highly angular corners, high bearing capacity, a large number of voids, and superlative resiliency. Sub-ballast is commonly a mixture of broadly graded sand and gravel. Ballast particles are obtained by crushing and blasting parent rocks such as basalt, gneiss, dolomite, granite, graphite, and so on. Commonly in Sri Lanka, ballast material is obtained from biotite gneiss. Ballast absorbs the loads and vibration exerted by moving trains and transmits and distributes it to underlying layers in a wide area at an acceptable level. It also acts as a level and hard bed for sleepers and holds sleepers in place. The ballast layer holds the rail track in position by giving longitudinal and transverse stability and makes small alterations in the level and the alignment of the track. It drains the rainwater instantly through its interconnected larger voids, also hindering the growth of vegetation in tracks.